Estimation of indoor radon from concrete blocks used In construction of wall in typical Nigerian dwellings (2012)
Radon gas is the most important source of natural radiation. Indoor radon concentration is the main path of human exposure to high radon concentration. Radon contribution from concrete block walls of typical Nigerian dwellings has been estimated from gamma ray spectroscopy measurements of radium concentration using generic equation. The radon concentrations varied from 11.27 Bq m-3 for a dwelling of dimensions 4.8 m × 4.8 m and 18.52 Bq m-3 for a dwelling of 3.6 m × 3.6 m. The effective dose varied from 0.28 to 0.47 mSv. All the results obtained are lower than the world average radon concentrations. The radiological hazard associated with the samples of building blocks considered in this study is not significant.